Assessing the Potential Impacts of the Tax Reform for Acceleration and Inclusion and the Build Build Build Program - Cororaton, Caesar (Animo Repository, 2019)
The Tax Reform for Acceleration and Inclusion (TRAIN) Act has prompted key changes in the personal income tax regime through excise taxes on most goods such as petroleum, sugar-sweetened beverages, and automobiles. The TRAIN was implemented to generate funds for the Build Build Build (BBB) program and at the same time to address income inequality and poverty. This paper aims to assess the potential growth, poverty, and distributional effects of the TRAIN Package 1 and the BBB Program using a computable general equilibrium model with poverty simulation. Results suggest that TRAIN I has prompted additional revenue in social programs and infrastructure spending. There are clear increases in the capital stock which drive economic growth with the industry sector leading the way and the services and agricultural sectors lagging behind. With regard to the inflationary effects, we can see that the additional excise taxes increase inflation in 2018 and 2019 but decelerates after that as higher growth would significantly dominate the inflationary effects. Results of the poverty and distributional microsimulation showed that the policy had reduced poverty and reduced income inequality very slightly. Assuming that the old tax regime is retained while implementing the other changes, the effect will be higher government revenue which may prompt higher spending and allocation to additional social programs and infrastructure in addition to higher economic growth and greater reductions in poverty.